2016
DOI: 10.2174/1389201017666160709202124
|View full text |Cite
|
Sign up to set email alerts
|

Memory Enhancing Effect of Black Pepper in the AlCl3 Induced Neurotoxicity Mouse Model is Mediated Through Its Active Component Chavicine

Abstract: The study revealed that BP improves memory and chavicine is a lead compound producing pharmacological effects of BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…It was originally designed to test the ability of rats to learn and remember the position of a hidden platform in an opaque water pool relative to external cues. In agreement with Thenmozhi et al (2015) and Iqbal et al (2016), our results suggest that AlCl3-intoxicated rats took longer to reach the platform compared to control rats during the acquisition phase, and during the probe the intoxicated rats have a significantly lower latency in the NO frame compared to control rats (Fig 4,5 and 6). Experiments have shown that the use of AlCl3 leads to a decrease in learning and memory capacity and to a dysfunction of cholinergic neurons.…”
Section: Morris Pool Testsupporting
confidence: 88%
“…It was originally designed to test the ability of rats to learn and remember the position of a hidden platform in an opaque water pool relative to external cues. In agreement with Thenmozhi et al (2015) and Iqbal et al (2016), our results suggest that AlCl3-intoxicated rats took longer to reach the platform compared to control rats during the acquisition phase, and during the probe the intoxicated rats have a significantly lower latency in the NO frame compared to control rats (Fig 4,5 and 6). Experiments have shown that the use of AlCl3 leads to a decrease in learning and memory capacity and to a dysfunction of cholinergic neurons.…”
Section: Morris Pool Testsupporting
confidence: 88%
“…Plants with large amounts of biologically active compounds could be used for the prevention and treatment of neurological disorders such as AD ( 18 19 ). Several studies have shown the beneficial effects of separate administration of PN and CZ extracts in different models of memory impairment ( 6 7 11 12 ). However, no one before has looked at the effect of co-administration of these extracts on memory performance.…”
Section: Discussionmentioning
confidence: 99%
“…We used an eight-day treatment here, while other studies have extended this period to as many as four weeks. ( 6 33 ). One reason for not extending the period of treatment with pepper is the irritating action of this plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the inhibition Alkaloids are the main class produced by the shikimic acid pathway present in black pepper, especially the piperamides [94]. These metabolites are present in the fruits and seeds of black pepper, and have wide pharmacological applicability, such as in antimetastatic, antidepressant, hepatoprotective and antitumor activities, and they also have neuroprotective effects [95,96]. Alkaloid concentrations and their biological properties are directly related to PAL activity in the plant [97,98].…”
Section: Homology Modeling and Molecular Docking To Fusariummentioning
confidence: 99%